2010
DOI: 10.4062/biomolther.2010.18.4.363
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Leptin in Cancer Progression

Abstract: -Growing evidence suggests a prominent role for leptin in human cancer progression. The intricate pattern of leptin cross-talk with other associated signaling pathways is a critical area of research that will ultimately contribute to comprehending the role of leptin in cancer progression. This review summarizes a portion of the current understanding of leptin signaling, with a critical focus on its contribution to tumor cell invasion and metastasis. Five topics are addressed in this review: (1) Leptin receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 118 publications
0
3
0
Order By: Relevance
“…Interestingly, although this protein is mainly secreted by adipocytes, it can also be expressed by pathologically altered cells, such as cancer cells ( 19 , 20 ). Thus, malignant cells can regulate their metabolic activities ( 21 ), promoting uncontrolled cell growth via Wnt/β-catenin ( 22 ), migration, invasion and angiogenesis ( 15 , 23 ), and downregulating apoptosis through a Bcl-2-dependent mechanism ( 21 , 24 ). Accordingly, leptin overexpression is detected in breast cancer cells and neighboring adipocytes, contrasting with normal breast glandular epithelial cells ( 15 , 25 ), promoting the expression of several tissue factors ( 26 ), which suggest an oncogenic role for this adipocytokine ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, although this protein is mainly secreted by adipocytes, it can also be expressed by pathologically altered cells, such as cancer cells ( 19 , 20 ). Thus, malignant cells can regulate their metabolic activities ( 21 ), promoting uncontrolled cell growth via Wnt/β-catenin ( 22 ), migration, invasion and angiogenesis ( 15 , 23 ), and downregulating apoptosis through a Bcl-2-dependent mechanism ( 21 , 24 ). Accordingly, leptin overexpression is detected in breast cancer cells and neighboring adipocytes, contrasting with normal breast glandular epithelial cells ( 15 , 25 ), promoting the expression of several tissue factors ( 26 ), which suggest an oncogenic role for this adipocytokine ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…These observations prompted us to speculate whether E11 deficiency leads to altered expression of leptin, a pleiotropic adipocytokine that is known to be associated with obesity, adipose tissue inflammation, and cancer ( Myers et al, 2010 ; Abella et al, 2017 ; de Candia et al, 2021 ). In addition to adipocytes, Leptin was found to be expressed in normal epithelial and carcinoma cells and subsequently promotes tumor growth through autocrine and paracrine signaling ( Lin and Hsiao, 2021 ; Kang and Moon, 2010 ). Indeed, we found that the level of leptin transcript was increased by E11 deficiency in the VAT and liver tissues as well as in MEFs ( Figure 6A and Figure 6—figure supplement 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…These observations prompted us to speculate whether E11 deficiency leads to altered expression of leptin, a pleiotropic adipocytokine that is known to be associated with obesity, adipose tissue inflammation and cancer (65)(66)(67). In addition to adipocytes, Leptin was found to be expressed in normal epithelial and carcinoma cells and subsequently, promotes tumor growth through autocrine and paracrine signaling (68,69). Indeed, we found that the level of leptin transcript was increased by E11 deficiency in the VAT and liver tissues as well as in MEFs (Fig.…”
Section: E11 Deficiency Leads To Elevated Production Of Leptin a Nove...mentioning
confidence: 99%